Reading-identity in the school environment - Rosa, Daniele Oliveira; Maia, Paulo Cezar (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
One of the persistent themes approached in primary school is the lack or difficulty of reading by Brazilian students. The low performance in external evaluations reveals the need to find a way to improve work in schools, ensuring the student's full learning. The aim of this article is to present a research project that has been developed in elementary schools in the State of Rio de Janeiro, with the objective of training readers through Literature reading workshops, which propose intersemiotic translations of literary texts for the audiovisual, centered on polytechnic work with formative character as a participatory methodology (Maia, 2020). These workshops result in student engagement, as they use the technological resources that are part of their daily lives and stimulate them through literary reading to observe, interpret, analyze and produce scripts to translate the text in a meaningful way. This creative power arises from the autonomy that this whole process allows. Therefore, the collective work environment in which literature provides possibilities for understanding and creating within a transdisciplinary perspective contributes to the improvement of education and social transformation.